2013
DOI: 10.1179/1476830513y.0000000066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc supplementation on efficacy of antidepressant therapy, inflammatory cytokines, and brain-derived neurotrophic factor in patients with major depression

Abstract: Zinc supplementation in conjunction with antidepressant drugs might be beneficial for reducing depressive symptoms. However, its effect does not appear to be mediated through impact of zinc on inflammatory processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 51 publications
2
53
1
3
Order By: Relevance
“…Conversely, chronic treatment with zinc, similar to conventional antidepressants, (Balu et al, 2008;De Foubert et al, 2004) was reported to increase BDNF mRNA and protein levels in the hippocampus (Cieslik et al, 2011;Sowa-Kucma et al, 2008) or cerebral cortex (Nowak et al, 2004) of rats. Interestingly, clinical studies also report that while zinc monotherapy (30 mg for 12 weeks) increased serum BDNF levels and decreased depressive symptoms in overweight or obese subjects (Solati et al, 2014), zinc supplementation (25 mg for 12 weeks) combined with selective serotonin reuptake inhibitor antidepressants reduced depressive symptoms, but did not change plasma levels of BDNF (Ranjbar et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, chronic treatment with zinc, similar to conventional antidepressants, (Balu et al, 2008;De Foubert et al, 2004) was reported to increase BDNF mRNA and protein levels in the hippocampus (Cieslik et al, 2011;Sowa-Kucma et al, 2008) or cerebral cortex (Nowak et al, 2004) of rats. Interestingly, clinical studies also report that while zinc monotherapy (30 mg for 12 weeks) increased serum BDNF levels and decreased depressive symptoms in overweight or obese subjects (Solati et al, 2014), zinc supplementation (25 mg for 12 weeks) combined with selective serotonin reuptake inhibitor antidepressants reduced depressive symptoms, but did not change plasma levels of BDNF (Ranjbar et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…IL-6R is a substrate of both types of ADAM proteases, whereas ADAM17 is primarily involved in generating sIL-6R and initiating IL-6 trans-signaling during pathological conditions. The shedding of IL-6R is further induced by phorbol ester phorbol-12-myristate-13-acetate, Opposing evidence [193] Zinc sulfate (25 mg/day) + SSRI (n = 20), placebo + SSRI (n = 17)…”
Section: Optimization Of Anti-il-6 Treatment Approaches In Mdd Via Sementioning
confidence: 92%
“…We did not include studies measuring the effect of non-pharmacological depression treatments or studies with the use of ketamine or pharmacological agents not registered as antidepressants. We did however partially include some studies (Brunoni et al 2014, Ranjbar et al 2014, Hernandez et al 2014, Abbasi et al 2012, Mackay et al 2009, Jazayeri et al 2010) examining the effect of other than antidepressant therapies with the control group (e.g. treated with an SSRI) meeting our inclusion criteria.…”
Section: Systematic Search and Criteriamentioning
confidence: 99%